Analisis Efektivitas Program JKN - Tiara Putri Hartanto; Aprilia Puji Astuti; Niken Rahmita; Elsa Saqila Al Fathikha; Ewalde Yovita Bria; Fina Nikmatul Wasi’ah; Abdul Latif; Alfu Laila; Bella Fevi Aristia; Eka Putri Nurhidayah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The National Health Insurance Program (JKN) organized by BPJS Health aims to improve access and quality of health services for all levels of Indonesian society. This research examines the effectiveness of the JKN program, with a focus on the use of the JKN mobile application, program implementation in health facilities, and factors that influence service quality. Based on case studies in several regions, the research results show that the JKN mobile application makes it easy for participants to access health-related services and information, although there are still obstacles such as a lack of public understanding of the application and technical problems. Apart from that, health services in hospitals and community health centers still face challenges such as a shortage of medical personnel, delays in services, and timeliness in administrative processes. Although the JKN program has expanded access to services, challenges in equal distribution of service quality and health resources still need to be overcome. Overall, the JKN program plays an important role in improving people's health and welfare, but improvements are needed in terms of community understanding, infrastructure and service efficiency to achieve more optimal and equitable health goals throughout Indonesia.